Clinicopathological features of primary leiomyosarcoma of the gastrointestinal tract following recognition of gastrointestinal stromal tumours. Issue 2 (13th June 2013) - Yamamoto, Hidetaka; Handa, Mizuki; Tobo, Taro; Setsu, Nokitaka; Fujita, Kohei; Oshiro, Yumi; Mihara, Yumi; Yoshikawa, Yasuji; Oda, Yoshinao
<x xml:space="preserve">Abstract</x> Aims We aimed to elucidate the clinicopathological and immunohistochemical features of leiomyosarcoma (LMS) of the gastrointestinal (GI) tract. Methods and results We encountered seven cases of GI‐LMS in the colon (n = 4), rectum (n = 1), jejunum (n = 1) and stomach (n = 1). They ranged from 1 to 25 cm (median, 8.5 cm) in size and had high mitotic counts (median 38 per 50 high‐power fields). Morphologically, the tumours were composed mainly of spindle cells with eosinophilic cytoplasm and various degrees of nuclear atypia and pleomorphism. Immunohistochemically, the tumours were positive for α‐smooth muscle actin (86%), muscle‐specific actin (71%), desmin (86%), calponin (71%), h‐caldesmon (57%) and smoothelin (71%). All were negative for KIT, CD34, protein kinase C theta and DOG1. Local recurrence and distant metastasis occurred in one and three patients, respectively. We then reviewed 55 cases of GI‐LMS from the era following the recognition of gastrointestinal stromal tumours. Among 29 of 55 cases for whom follow‐up information was available, the estimated 5‐year overall survival rate was 51.6%; tumour size ≥5 cm was correlated significantly with shorter overall survival time (P = 0.0016), while mitotic count (≥50 or ≥100 per 50 high‐power fields) proved to be no prognostic factor. Conclusions GI‐LMSs have distinctive clinicopathological and immunohistochemical features and exhibit aggressive biological behaviour.